Persepsi Masyarakat Desa terhadap Fenomena Politik Uang dalam Pemilihan Umum - Nabilah, Rifa; Afrizal, Stevany; Bahrudin, Febrian Alwan (Jurnal Publisitas, 2022)
Money politics is now considered a "custom" in the Maja community. Even in rural communities who have strong solidarity, money politics is considered to have a strong role to bind people's voices in political contestation. The purpose of this study was to determine how the public's perception of the phenomenon of money politics. in Maja Village, Maja District, Lebak Regency. The research method used is qualitative. The results of the study indicate that the people of Maja Village have different perceptions from legal norms in viewing money politics. The community considers that money politics is a form of gratitude for the votes that will be given and an approach to the community. In social action theory, Weber introduced the concept of a verstehen approach to understanding the meaning of one's actions. In this case, the Maja people build perceptions and action decisions based on their vision of the people around them and the figures they emulate.